Dampak Stres pada Kesehatan - Qonita, Adzrok; Setiorini, Anggi; Ratna, Maya Ganda; Zuraida, Reni (CV. Jasa Sukses Abadi, 2024)
Stress is a bodily response to a stressor, which refers to any condition perceived as threatening or causing pressure. Stress can have both positive (eustress) and negative (distress) effects. Prolonged distress can affect various body systems through the activation of the Hypothalamus-Pituitary-Adrenal (HPA) axis and the Sympathetic-Adreno-Medullary (SAM) axis. Activation of these axes triggers the release of cortisol, epinephrine, and norepinephrine, leading to physiological and behavioral changes. Stress impacts multiple organ systems, including the cardiovascular, respiratory, gastrointestinal, hepatobiliary, urinary, reproductive, musculoskeletal, integumentary, sensory, and immune systems. It also affects sleep quality and mental health. In the cardiovascular system, stress can cause hypertension, atherosclerosis, and an increased risk of heart disease. In the respiratory system, stress worsens asthma and increases the risk of airway infections. In the gastrointestinal system, stress triggers digestive disorders, such as gastritis and peptic ulcers, due to increased stomach acid production and inflammatory mediators. Stress affects the hepatobiliary system by impairing liver function through increased inflammation. In the urinary system, stress can cause dysfunctions such as enuresis and increased urination frequency. In the reproductive system, stress can result in menstrual disorders in women and decreased testosterone levels in men. The musculoskeletal system can be affected by excessive muscle contractions, leading to pain and muscle fatigue. Stress impacts the integumentary system, triggering conditions such as acne, psoriasis, and alopecia areata. It can also cause sensory system disorders, affecting hearing, taste, and vision. In the immune system, stress suppresses immune responses, increasing susceptibility to infections and prolonging wound healing. Prolonged stress negatively impacts both physical and mental health, highlighting the importance of understanding the mechanisms through which stress affects the body to reduce the risk of serious health problems.